Parylene C as a versatile dielectric material for organic field-effect transistors - Marszalek, Tomasz; Gazicki-Lipman, Maciej; Ulanski, Jacek (Beilstein journal of nanotechnology, 2017)
Beilstein Journal of Nanotechnology